An automated earthquake detection and characterization tool for rapid earthquake and tsunami response in Western Mediterranean. Issue 2 (20th March 2023) - Menager, Marine; Guilhem Trilla, Aurélie; Delouis, Bertrand
SUMMARY: A method of moment tensor inversion with a grid search on the source location and time is presently considered by the French Tsunami Service Provider (TSP or CENALT in French) for rapid earthquake and tsunami warning in the western Mediterranean Sea and the North-East Atlantic Ocean. The approach follows the GRiD MT (Grid-based Real-time Determination of Moment Tensors) methodology already implemented in other regions. Here, we show developments made towards its implementation for moderate to large earthquakes in the Ibero–Maghreb region, which is prone to generate tsunamis in the western Mediterranean Sea. Results obtained for a dozen of events, contrasting in magnitudes, locations and focal mechanisms, validate the choices made for the inversion parameters (grid resolution, frequency band, velocity models, etc.). Their source solutions are compared to published solutions from seismological institutes including GFZ and USGS. Besides, we describe the special care needed for a correct real-time event detection analysis, and in particular for obtaining the most appropriate source solution out of the thousand ones explored by the method. Rapid GRiD MT solutions can in turn be used for rapid tsunami simulations run by the TSP operator.